Breastfeeding for Gut Infant Health - Badriul Hegar; Yvan Vandenplas (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Infants react sensible to dietary changes because the gut physiology and functionality is not fully mature. The first few months of life is the 'window of opportunity' for optimal physical growth and development, cognitivedevelopment, and emotional and social development. Exclusive breastfeeding is recommended for the first 6 months of life. Breast milk is important for the maturation of the infant’s digestive system. Potentially protectivefactors are present in higher amounts in feces from breast-fed infant than from formula-fed infants. The amount of intestinal bifidobacteria in breastfed infants is higher than in formula-fed babies. Mother's milk protects againstinfection because it contains different factors with immologic properties. The differences in protein fractions between human and cow milk are impressive. The human milk oligosaccharides are the third most important nutritional component are fermented in the colon, making the environment in the colon suitable for the growth of bifidobacteria and lactobacillus.